2016
DOI: 10.1177/1477153515616166
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the chromatic contribution to recognition of facial expression

Abstract: A pedestrian may judge the intentions of another person by their facial expression amongst other cues and aiding such evaluation after dark is one aim of road lighting. Previous studies give mixed conclusions as to whether lamp spectrum affects the ability to make such judgements. An experiment was carried out using conditions better resembling those of pedestrian behaviour, using as targets photographs of actors portraying facial expressions corresponding to the six universally recognised emotions. Responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…[6][7][8][9][10][11][12] Further studies have sought judgements when targets are presented at one or more fixed distances. [13][14][15][16][17][18][19][20] The stop-distance procedure reveals the distance at which a task could be completed, but does not reveal whether that distance approximates that at which it is desirable for pedestrians after dark. Experiments seeking judgements at fixed distances may exhibit better ecological validity but only if the distances used in trials include (or bracket) that which approximates pedestrians' desired distance for evaluating other people.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Further studies have sought judgements when targets are presented at one or more fixed distances. [13][14][15][16][17][18][19][20] The stop-distance procedure reveals the distance at which a task could be completed, but does not reveal whether that distance approximates that at which it is desirable for pedestrians after dark. Experiments seeking judgements at fixed distances may exhibit better ecological validity but only if the distances used in trials include (or bracket) that which approximates pedestrians' desired distance for evaluating other people.…”
Section: Introductionmentioning
confidence: 99%
“…68 Subsequent research first examined methodology, proposing that different procedures may lead to different conclusions, 161,162 that facial emotion recognition from expression is a more suitable task than identify recognition, [163][164][165] that a brief duration of 500 ms better resembles typical behaviour than does continuous observation, 166,167 and that the stop-distance approach used in many studies may not lead to the same conclusions as evaluations made at the desirable observation distance of 15 m. 166,167 In studies carried out using facial emotion recognition, SPD is not suggested to be a critical parameter. [168][169][170][171] One question still to be resolved is whether a measure of vertical illuminance is needed to characterise this task or whether it is safe to assume that horizontal illuminance at the road surface is sufficient.…”
Section: Comparing Approachesmentioning
confidence: 99%
“…Three studies were carried out using a facial emotion recognition task, with targets sized to simulate interpersonal distances including 15 m and presented for limited durations (500 ms and 1000 ms) [Fotios et al, 2015b, 2015c. It is concluded in these studies that lamp spectrum does not affect facial emotion recognition, a conclusion which disagrees with that conveyed by Peña-García et al Figure 2 shows the results from Yang and Fotios [2015] in which 20 test participants evaluated expressions in 24 target images under 72 combinations of lamp (three lamps of different colour characteristics), luminance (6), duration (2) and distance (2).…”
Section: Facial Recognitionmentioning
confidence: 99%